(untitled) (Historia, 2021)
Winburg, established in 1842, is the oldest town in South Africa’s Free State Province and geographically, a central town in this province and in the country. Originally a Voortrekker town, it was, from 1845 until 1854, under British rule, before becoming part of the newly established Oranje-Vrijstaat (Orange Free State) Boer/Afrikaner republic. When the South African War (also known as the Anglo-Boer War, but here the author chooses to call it the South African War) broke out on 11 October 1899, the large Winburg commando went off to fight on the Natal front, and later in the Orange Free State.